Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00239-017-9813-9
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Evolutionary History of the CAP Superfamily of Proteins Using Amino Acid Sequence Homology and Conservation of Splice Sites

Abstract: Proteins of the CAP superfamily play numerous roles in reproduction, innate immune responses, cancer biology, and venom toxicology. Here we document the breadth of the CAP (Cysteine-RIch Secretory Protein (CRISP), Antigen 5, and Pathogenesis-Related) protein superfamily and trace the major events in its evolution using amino acid sequence homology and the positions of exon/intron borders within their genes. Seldom acknowledged in the literature, we find that many of the CAP subfamilies present in mammals, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 117 publications
0
19
0
Order By: Relevance
“…The CAP superfamily proteins are well distributed in all organisms, where they display a variety of functions [98]. This superfamily includes three major groups of proteins: cysteine-rich secretory proteins (CRISP), antigen or allergen proteins from arthropod venoms, and pathogenesis-related proteins from plants (PR) [99]. The CRISP proteins and antigen/allergen proteins have been described in venoms [100].…”
Section: Resultsmentioning
confidence: 99%
“…The CAP superfamily proteins are well distributed in all organisms, where they display a variety of functions [98]. This superfamily includes three major groups of proteins: cysteine-rich secretory proteins (CRISP), antigen or allergen proteins from arthropod venoms, and pathogenesis-related proteins from plants (PR) [99]. The CRISP proteins and antigen/allergen proteins have been described in venoms [100].…”
Section: Resultsmentioning
confidence: 99%
“…For several CAP proteins, it has been shown that metal binding is critical for specific functions [14–17] and that two highly conserved histidines of the CAP tetrad co-ordinate Zn 2+ or other divalent metal ions. GAPR-1 consists almost exclusively of a CAP domain and the GAPR-1 subfamily was recently described to be the earliest evolutionary ancestor within the CAP superfamily [18]. GAPR-1 is therefore a suitable model protein to study the CAP domain structure–function relationship.…”
Section: Introductionmentioning
confidence: 99%
“…GAPR-1 is the most ancient CAP subfamily member in vertebrates that evolved from the CAP/PR domain in bacteria 1,12 . These one-domain proteins evolved in invertebrates and mammals into proteins with two domains, connected via a hinge region.…”
Section: Introductionmentioning
confidence: 99%